(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Turkot T. І., Konoval O. А. Individualization of students-physicists’ independent work on principles of requirements for health-consciosness training. The article substantiates the necessity of individual independent work of students-physicists from a view of health-consciosness training as the condition to keep young people healthy. To implement the principle of an individual approach means considering the style of educational activity. The authors characterize the typological groups of students, define the methods of their independent educational activity while studying physics. These methods tend to optimally meet psychological features of these groups.